Management of Open Tile C Pelvic Fractures and Their Outcomes: A Retrospective Study of 30 Cases - Lu S; Liu F; Xu W; Zhou X; Li L; Zhou D; Li Q; Dong J (Dove Medical Press, 2022)
Shun Lu,1 Fanxiao Liu,1 Weicheng Xu,1 Xiaofeng Zhou,2 Lianxin Li,1 Dongsheng Zhou,1 Qinghu Li,1 Jinlei Dong1 1Department of Orthopaedics Surgery, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan City, Shandong Providence, People's Republic of China; 2Department of Orthopaedics Surgery, Shandong Provincial Hospital, Cheeloo College of Medicine, Shandong University, Jinan City, Shandong Providence, People's Republic of ChinaCorrespondence: Qinghu Li; Jinlei Dong, Department of Orthopaedics, Shandong Provincial Hospital affiliated to Shandong First Medical University, Jinan City, Shandong Providence, People's Republic of China, Tel +8613402214695 ; +861509874540, Email sdliqinghu@163.com; dongjinlei@163.comBackground: Open Tile C pelvic fractures are particularly severe. However, reports on their management and outcomes are relatively rare. This study analyzed the demographic and clinical characteristics of patients with open Tile C pelvic fractures and describes our management and outcomes of these injuries.Methods: This retrospective review included all patients with open Tile C pelvic fractures treated in our department between January 2014 and June 2021. Data on patient demographics, characteristics of the injuries, surgical management, and outcomes were analyzed.Results: Thirty patients with a mean age of 34.0 years met the diagnostic criteria. The average Injury Severity Score was 40.3. According to the Tile fracture classification, 6 patients sustained type C1.1, 12 sustained type C1.2, 3 sustained type C1.3, 5 sustained C2 and 4 sustained type C3. Most patients had soft tissue injuries in multiple zones. All patients sustained associated injuries. Management consisted of bed rest in 8 cases, external fixation as the final strategy in 14, conversion from external fixation to internal fixation in 3, open reduction with internal fixation in 5, and amputation in 6. The average amount of packed red blood cells transfused was 33.3 units, the average intensive care unit stay was 11.3 days, the mean number of operations required was 6.2, and the mean length of hospital stay was 81.8 days. The main complications were early soft tissue infections and venous thrombosis. One patient died of sepsis and multi-organ failure. Soft tissue injuries in multiple zones increased utilization of hospital resources whereas anorectal injuries did not. Vascular damage accompanying truck crush injuries had a high amputation rate.Conclusion: Open Tile C pelvic fractures require multidisciplinary diagnosis and management and consume considerable hospital resources. More emphasis needs to be placed on this complex injury.Keywords: open tile C fractures, management, outcomes